1996
DOI: 10.1038/381307a0
|View full text |Cite
|
Sign up to set email alerts
|

A complete skeleton of the giant South American primate Protopithecus

Abstract: A complete skeleton of a large-bodied New World monkey has been found in Pleistocene cave deposits in the Brazilian state of Bahia. It demonstrates an unprecedented combination of body size, locomotor and cranial morphology. Skeletal features indicate an animal of approximately 25 kg, more than twice the mass of any living South American monkey. We refer the specimen to Protopithecus brasiliensis Lund, 1838, a large Pleistocene primate originally represented by only a proximal femur and distal humerus. The ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 6 publications
2
74
0
4
Order By: Relevance
“…These include Cebus, Saimiri, callitrichines, and atelines (Kay 1990(Kay , 1994Rosenberger & Strier, 1990;Ford & Davis, 1992;Rosenberger, 1992;Cartelle & Hartwig, 1996). For example, Ford & Davis (1992:438-439) surmise that over the course of platyrrhine evolution capuchin monkeys have "nearly tripled in body size .. .independent of all other New World monkey lineages."…”
Section: Misconception #7 Callitrichines Are Dwarfsmentioning
confidence: 94%
See 1 more Smart Citation
“…These include Cebus, Saimiri, callitrichines, and atelines (Kay 1990(Kay , 1994Rosenberger & Strier, 1990;Ford & Davis, 1992;Rosenberger, 1992;Cartelle & Hartwig, 1996). For example, Ford & Davis (1992:438-439) surmise that over the course of platyrrhine evolution capuchin monkeys have "nearly tripled in body size .. .independent of all other New World monkey lineages."…”
Section: Misconception #7 Callitrichines Are Dwarfsmentioning
confidence: 94%
“…Saimiri, in contrast, has probably undergone a significant body size reduction in comparison to its nearest early Miocene fossil relative Dolichocebus (Rosenberger, 1990). Relatives of spider and howler monkeys were, in the recent past, twice as large as any remaining alive today (Cartelle & Hartwig, 1996;Hartwig & Cartelle, 1996). Although it is unclear how frequently increases and especially decreases in body size have occurred in platyrrhine evolution, these events appear to have played a major role in shaping the reproductive, mating, and social systems of New World primates (Ford & Davis, 1992;Martin, 1992;Garber, 1994).…”
Section: Misconception #7 Callitrichines Are Dwarfsmentioning
confidence: 98%
“…but do not resolve the timing of cladogenesis within Atelidae (Hartwig, 1993;Cartelle and Hartwig, 1996;Hartwig and Cartelle, 1996;Jones, 2008). C. Cebidae -The extant family Cebidae includes two subfamilies, the Cebinae (Cebus, Saimiri and Aotus) and the Callitrichinae (tamarins and marmosets).…”
Section: Crown Platyrrhinesmentioning
confidence: 99%
“…Many studies have indicated that taxa of large body size can be prone to extinction, especially at the hands of humans (Brown, 1971;Caughley and Gunn, 1996;Godfrey et al, 1997;Harcourt, 1999;Hartwig and Cartelle, 1996;Jolly, 1986;Martin, 1984;McKinney, 1997;Richard and Dewar, 1991;Vermeij, 1986). Because so many aspects of a species' biology correlate with body size (CluttonBrock and Harvey, 1983;Jungers, 1985), several mechanisms for the correlation of probability of extinction with body size have been suggested.…”
Section: Traits Of Susceptibilitymentioning
confidence: 96%